Ranking clinical indicators for stroke pattern identification according to clinical importance in traditional Korean medicine - Park, Tae-Yong (Int J Clin Exp Med, 2014)
Differences in the value that individual clinicians place on each clinical indicator, when performing pattern identification, can be a significant obstacle in achieving accurate and consistent pattern identification. In this study, we aimed to identify and rank the importance of clinical indicators that correspond to each pattern. During the fundamental study to standardize and objectify the identification of patterns in traditional Korean medicine (TKM) treatment for stroke (the SOPI-Stroke project), we developed the Third Standardization for Pattern Identification (K-SPI-Stroke-III), which includes 44 clinical indicators that belong to one of the four patterns (Dampness-Phlegm, Fire-Heat, Qi deficiency, and Yin deficiency). Between September 2006 and December 2010, a total of 105 TKM doctors from 11 hospitals performed four examinations on 4,012 subjects based on the clinical indicators in the K-SPI-Stroke-III, and they were asked to leave a special mark on the indicators they thought were important, regardless of the number of the indicators. A total of 1,018 patients were included in the study. Among the 44 clinical indicators of the K-SPI-Stroke-III, four indicators were highly significant in differentiating between patterns and the frequency within a pattern. In contrast, another seven indicators were almost useless. Meanwhile, six confounding indicators had outlying values for differentiating between patterns and the frequency within a pattern. In conclusion, the four significant indicators should be actively considered when identifying patterns for strokes in clinical practice. Regarding the six confounding indicators, a further study should be conducted to modify some parts of the current K-SPI-Stroke-III.